Politiques de la fragmentation urbaine et violence, l’exemple de Kingston, Jamaïque - Romain Cruse (Unité Mixte de Recherche 8504 Géographie-cités, 2010)
This paper deals with spatial division as a key feature for understanding Jamaican capital’s Kingston. Segmentation appears in the socioeconomical and political spaces as well as in ethnicities. Here are actors and interest at stakes exposed. The geopolitical analysis shows victims (poor/black people from downtown Kingston) and beneficiaries (local politicians and wealthy businessmen). Although patterns driving economical, political and ethnic segregation are quite obvious – and responsibilities well known –, the cultural sphere highlights a subtle form of reproduction. This is locally known as « Willy Lynch syndrome ».